Pengukuran Kinerja Pegawai Dinas Pekerjaan Umum Provinsi Maluku Dalam Pemanfaatan Sistem Informasi Dengan Menggunakan IT Balanced Scorecard - Syeni Novianti Ferdinandus; Augie David Manuputty (Universitas Budi Darma, 2021)
The public works office of Maluku province is one of the public bodies that has the task of carrying out the affairs of the local government. The purpose of the research is to find out the extent of contribution and utilization through IT applications in supporting employee performance needs. This study uses IT Balanced Scorecard method as a means of measuring clearly, monitoring and optimizing the realization of business values or benefits and benefits of Information Technology where IT Balanced Scorecard has 4 perspectives (Organizational Contribution Perspective, User Orientation Perspective, Operational Excellence Perspective, and Future Orientation Perspective). The research method that will be used in The Measurement of Performance of Public Works Service Employees is mixed methods. In this study, data collection was obtained through interviews, observations, and dissemination of questionnaires to a selected number of respondents based on their abilities and relevant to their work. This study showed the measurement value of Organizational Contribution by 23 percent, User Orientation by 19 percent, Operations by 21 percent, and Future Orientation by 20 percent and for the average result of the IT Balanced Scorecard value is 85 percent. In the employee measurement results, the highest perspective is organization contribution by 23 percent, and the lowest perspective is User Orientation by 19 percent. Thus, it indicates that the employee as a user is not adequate in the activities for the future. The ability and expertise of employees still have limitations with a number of obstacles in organizing the system appropriately. Therefore, it is necessary to improve the competence and expertise in the training provided. And also satisfaction in using information system applications need to be improved again so as to be able to face the changes to come.